Bioremediation of chromium (VI) by a microbial consortium isolated from tannery effluents and their potential industrial application - Bhattacharjee, Arghyadeep; Chaudhuri, Rajarshi; Pandey, Priyanshu; Mitra, Arup Kumar (Journal of Environmental Engineering and Landscape Management, 2021)
West Bengal has several leather industries and as such huge amount of leather are processed every year. The tannery effluents are discharged into the land and open water causing soil and water pollution respectively. Chromium is one of the most toxic inorganic contaminants which is well known for its carcinogenicity. Thus, our study focuses on investigating the bioremediation potential of common microflora isolated from tannery wastewater. In our study, Isolate 1 has the highest ability to reduce chromium (Cr6+) as compared to others. Isolate 4 has the highest protease, lipase and leather degradation activities. Isolate 1 shows the maximum keratinase activity making it an effective strain for keratinase production. Also, it has been found that pH 8 and temperature 40 °C was most suitable for keratinase production. Owing to the multidimensional ability of these two isolates, they were identified by 16S rRNA sequencing and it reveals that Isolate 1 and Isolate 4 belong to Bacillus cereus F4810/72 and Brevibacillus brevis F4810/72 respectively. Thus, this study establishes the role and efficiencies of these microorganisms in combatting pollution, particularly in the water bodies in which harmful chemicals leak regularly owing to improper waste management by various industries.Please view correction statement: Corrigendum: Bioremediation of chromium (VI) by a microbial consortium isolated from tannery effluents and their potential industrial application